Spiritual attainment - International Conference on Spritual Science (2004: Shri Janannath Sanskrit Vishvavidyalaya); Dash, Keshab Chandra (Delhi : Pratibha Prakashan, 2006)
Contributed seminar papers
Includes bibliographical references and index
English and Sanskrit
Keywords: Spiritual life -- Hinduism -- Congresses; Philosophy and religion -- India -- Congresses; Hinduism -- Doctrines -- Congresses